1999
DOI: 10.1002/(sici)1096-8628(19990212)82:4<294::aid-ajmg4>3.3.co;2-l
|View full text |Cite
|
Sign up to set email alerts
|

Paternally derived de novo interstitial duplication of proximal 15q in a patient with developmental delay

Abstract: Interstitial duplications of proximal 15q containing the Prader-Willi syndrome/Angelman syndrome (PWS/AS) region have been found in patients with autism or atypical autism. In these cases with an abnormal phenotype, the duplications were maternally derived. Paternal origin of the duplication has been associated with a normal phenotype. We report on a patient who presented with nonspecific developmental delay and partial agenesis of the rostral corpus callosum. Fluorescence in situ hybridization (FISH) studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 0 publications
1
40
0
Order By: Relevance
“…Although less common, direct duplications of proximal 15q11-15q13 have been observed (Pettigrew et al 1987;Clayton-Smith et al 1993a;Browne et al 1997;Cook et al 1997Cook et al , 1998Mohandas et al 1999), some with the same breakpoints as PWS/AS deletions, whereas others have a more distal breakpoint similar to the large inv dup(15) (Repetto et al 1998;Robinson et al 1998). Patients with maternal duplications that include at least the PWS/AS critical region show devel-opmental delay, or autism (Browne et al 1997;Cook et al 1997Cook et al , 1998Repetto et al 1998), whereas a few individuals with paternal duplications have a nonspecific developmental delay (Mohandas et al 1999).…”
Section: Other 15q11-15q13 Rearrangementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although less common, direct duplications of proximal 15q11-15q13 have been observed (Pettigrew et al 1987;Clayton-Smith et al 1993a;Browne et al 1997;Cook et al 1997Cook et al , 1998Mohandas et al 1999), some with the same breakpoints as PWS/AS deletions, whereas others have a more distal breakpoint similar to the large inv dup(15) (Repetto et al 1998;Robinson et al 1998). Patients with maternal duplications that include at least the PWS/AS critical region show devel-opmental delay, or autism (Browne et al 1997;Cook et al 1997Cook et al , 1998Repetto et al 1998), whereas a few individuals with paternal duplications have a nonspecific developmental delay (Mohandas et al 1999).…”
Section: Other 15q11-15q13 Rearrangementsmentioning
confidence: 99%
“…Patients with maternal duplications that include at least the PWS/AS critical region show devel-opmental delay, or autism (Browne et al 1997;Cook et al 1997Cook et al , 1998Repetto et al 1998), whereas a few individuals with paternal duplications have a nonspecific developmental delay (Mohandas et al 1999). Finally, a few triplication cases have been reported (Schinzel et al 1994;Cassidy et al 1996;Long et al 1998;Robinson et al 1998), as well as paracentric inversions of 15q11-15q13 (Clayton-Smith et al 1993b).…”
Section: Other 15q11-15q13 Rearrangementsmentioning
confidence: 99%
“…Inherited int dup15 is rare, with only one published case involving the inheritance of a maternal duplication from the mother (Boyar et al, 2001), although some families with paternal duplication inherited from the father have been documented (Browne et al, 1997; Cook et al, 1997; Boyar et al, 2001; Veltman et al, 2005; Urraca et al, 2013; Al Ageeli et al, 2014). However, few cases of paternal duplication with developmental delay have been reported (Mohandas et al, 1999; Mao et al, 2000; Veltman et al, 2005). …”
Section: Introductionmentioning
confidence: 99%
“…Both paternal and maternal copies of this region are required for normal development, with loss of the paternal contribution leading to PWS and loss of the maternal contribution resulting in the AS phenotypes 13 . Surprisingly, Mohandas et al 18 reported a paternally derived de novo interstitial duplication of the proximal 15q containing the PWS/AS critical region in a patient with developmental delay, which raises the question as to whether or not all paternal duplications are benign with respect to phenotype. Mohandas et al 18 hypothesized that the breakpoints generating the 15q duplications, although clustered in the proximal 15q, may vary at the molecular level resulting in dosage changes for a different set of genes.…”
Section: Discussionmentioning
confidence: 99%